An algorithm for improved stability of DSL networks using spectrum balancing - Monteiro, Marcio; Gomes, Ana; Lindqvist, Neiva; Dortschy, Boris; Klautau, Aldebaro (IEEE Global Telecommunications Conference GLOBECOM 2010, Miami, FL, United States, 2010-12-06 - 2010-12-10, 2010)
The proper management of the signal to noise ratio margin is important for improving the stability of digital subscriber line (DSL) networks and increasing the customer satisfaction regarding services such as triple-play. This work presents a novel algorithm for multiuser margin optimization that benefits from the relationships between power and margin adaptation. The proposed multiuser margin maximization (MMM) is a meta algorithm that repeatedly invokes a spectrum balancing base algorithm. The base algorithm corresponds to a dynamic spectrum management (DSM) algorithm of level one or two, and is responsible for part of the overall spectra optimization procedure. Simulation results illustrate the performance of the proposed algorithm when using two base algorithms: iterative water-filling (IWF) and iterative spectrum balancing (ISB). The results show that the proposed MMM is able to design better noise margins and spectra, providing performance improvements when compared to a previous margin optimization algorithm that is restricted to using DSM level 1 coordination.